Factors Influencing the Utilization of Posyandu Services in the Work Area of Bah Biak Health Center, Pematangsiantar - Muharti Sanjaya (International Journal of Public Health Excellence (IJPHE), 2022)
Coverage of under-five weighing in posyandu is one of the high and low indicators of community participation in posyandu. The large number of mothers who do not know what programs are in the posyandu make the general public only know that the posyandu is only for immunization. In the city of Pematangsiantar the lowest coverage of weighing toddlers was found in the Bah Biak Health Center area of 19.03%. This research is a survey research with the type of explanatory research and aims to explain the influence of predisposing, supporting, and driving variables on posyandu utilization in the region. Work of the Bah Biak Health Center. The population in this study were all PUS women in the work area of the Lalang Village Health Center. Sampling was carried out by simple random sampling using a questionnaire and analyzed using a logistic regression test. The results showed that out of 140 respondents, 59 respondents (42.1%) used the posyandu and 81 respondents (57.9%) did not use the posyandu. Based on the results of the bivariate test in this study, it showed that the variables of knowledge (0.023), occupation (0.004), distance to health facilities (0.004), support for health workers (0.023), had a relationship with the utilization of posyandu in the Bah Biak Health Center area. Based on the results of the research, it is hoped that the posyandu managers will provide comprehensive information regarding both the program and the benefits that can be obtained from posyandu services. It is expected to increase collaboration between cadres and various parties, especially with community leaders and PKK women in posyandu activities with monitoring and guidance from the Lalang Village Health Center.